The Effectiveness of Resocialization - Sensitive Questions - Zdzisław Bartkowicz (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
The resocialization of the offender should be regarded as an ineffective activity considering the high rates of recidivism. Resocialization pedagogy, however, asks not only about the relapse into crime but also about favorable mental transformations that are the objective of educational and therapeutic measures. The still infrequent (longitudinal) studies on the psychic evolution taking place during the resocialization process show the low efficacy of measures, which does not, however, lead to a radical reform of resocialization institutions. The text shows the directions of research that might help in devising the ways to enhance the effectiveness of measures impacting the offender.